The influence of total physical inactivity on plasma homocysteine levels. Risk factor for development of cardiovascular disease - Mihaela Jurdana; Nadja Plazar; Rado Pišot (Exercise and Quality of Life)
Physical inactivity is the second most significant risk factor for chronic non-infectious contagious diseases in developed countries. However, conditions have slightly improved in the past few years; still, only 20 % of the population is being active in a fashion to reduce the probability of cardiovascular complications. Epidemiological research has confirmed that regular physical activity and nutrition containing sufficient quantities of folic acid, vitamins B6 and B12, reduce the level of homocysteine in blood. In our research, we studied the influence of long-lasting inactivity on the level of homocysteine and folic acid levels in blood. Ten male subjects were resting in horizontal position for 35 days in a clinical setting. After 35 days of resting we documented a statistically relevant increase in homocysteine level and decrease of folic acid concentration, despite supervised nutrition. We can conclude that prolonged physical inactivity is an autonomous, independent risk factor for the development of cardiovascular diseases.